2011 IEEE 23rd International Symposium on Power Semiconductor Devices and ICs 2011
DOI: 10.1109/ispsd.2011.5890806
|View full text |Cite
|
Sign up to set email alerts
|

Electro-thermal instability in multi-cellular Trench-IGBTs in avalanche condition: Experiments and simulations

Abstract: This paper reports on the results of a study on electro-thermal instability induced in multi-cellular TrenchIGBTs in avalanche condition. Experimental measurements, made on T-IGBTs, show possible inhomogeneous current distribution under Unclamped Inductive Switching (UIS) confirmed by transient infrared thermography measurements. Together with this, an analytical modeling of avalanche behavior has been included in a compact electro-thermal simulator to study the interaction between a large numbers of elementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…27). This method is beneficial to detections of fabrication defects instead of high current module tests like an SCSOA or a large current UIS [98,99]. Once the avalanche occurs around defects, the V CE rise halts due to charging the extra capacitor C. At the stop-moment of the current shunting to the C, small but all the current immediately flows into the IGBT.…”
Section: How To Identify Tough Chip In Test Sequencesmentioning
confidence: 99%
“…27). This method is beneficial to detections of fabrication defects instead of high current module tests like an SCSOA or a large current UIS [98,99]. Once the avalanche occurs around defects, the V CE rise halts due to charging the extra capacitor C. At the stop-moment of the current shunting to the C, small but all the current immediately flows into the IGBT.…”
Section: How To Identify Tough Chip In Test Sequencesmentioning
confidence: 99%
“…With this value of current in fact, device operates in negative differential resistance region and correct behavior of the implemented simulator can be evaluated in this condition. As effect of negative resistance, current distribution becomes non uniform during the time [10][11][12]. Initially device starts with uniform temperature and a current which is slightly non uniform due to differences in the layout and to parasitic elements.…”
Section: Avalanche Simulation In Negative Differential Resistance (Ndmentioning
confidence: 99%
“…[12][13][14][15]. In this case the final profile of the current density shows a creation of a hot-spot and all the current flows in a very small area, just after 6 ls.…”
Section: Avalanche Simulation In Negative Differential Resistance (Ndmentioning
confidence: 99%
“…Together with the need of increased performances there has recently been an increased request of reliability and, in recently many cases, ruggedness during avalanche operation. Recent the importance of investigating the avalanche ruggedness of IGBTs has been thoroughly investigated [1][2][3][4][5][6][7][8][9][10][11] by means of theoretical, numerical and experimental evidences. These investigations have demonstrated that failure during avalanche operation usually occur when current filaments are present in the device active area or in the termination region.…”
Section: Introductionmentioning
confidence: 99%